Central sterile supply departament management on hospital-associated infections: a systematic review and meta-analysis - Shuai, Jing; Liu, Maoyu; Hou, Jialing; Chen, Yu; Jiang, Jun; Yu, Jing; Yin, Liang (Revista do Instituto de Medicina Tropical de São Paulo, 2025)
ABSTRACT Hospital-associated infections (HAIs) pose significant risks in clinical settings, and sterile supply centers management plays a crucial role in infection control. This systematic review and meta-analysis aimed to evaluate the impact of supply center management on the incidence of HAIs and adverse events. The systematic review encompassed studies that compared supply center management protocols with standard care. The PRISMA guidelines were followed to search seven databases for relevant studies. The meta-analysis calculated pooled odds ratios (OR) for HAIs and adverse events, and heterogeneity was assessed using Tau2, Chi-squared, and I2 statistics. Eight studies were included in the final analysis, each assessing intervention efficacy. The results revealed a significant reduction in HAIs (pooled OR=0.3; 95%CI [0.19; 0.49]). Adverse events were also significantly reduced (pooled OR=0.15; 95%CI [0.09; 0.25]). Heterogeneity was low for both HAIs (Tau2=0.00; I2=0%) and adverse events (Tau2=0.04; I2=19%), which indicated a consistent effect across the studies. Sterile supply center management significantly reduced the incidence of HAIs and adverse events. This suggests these interventions are effective in improving clinical outcomes and could be a vital component of infection control strategies in healthcare facilities.